Wide‐field Stokes polarimetric microscopy for second harmonic generation imaging. Issue 5 (29th January 2023) - Uribe Castaño, Leonardo; Mirsanaye, Kamdin; Kontenis, Lukas; Krouglov, Serguei; Žurauskas, Edvardas; Navab, Roya; Yasufuku, Kazuhiro; Tsao, Ming‐Sound; Akens, Margarete K.; Wilson, Brian C.; Barzda, Virginijus
Abstract: We employ wide‐field second harmonic generation (SHG) microscopy together with nonlinear Stokes polarimetry for quick ultrastructural investigation of large sample areas (700 μm × 700 μm) in thin histology sections. The Stokes vector components for SHG are obtained from the polarimetric measurements with incident and outgoing linear and circular polarization states. The Stokes components are used to construct the images of polarimetric parameters and deduce the maps of ultrastructural parameters of achiral and chiral nonlinear susceptibility tensor components ratios and cylindrical axis orientation in fibrillar materials. The large area imaging was employed for lung tumor margin investigations. The imaging shows reduced SHG intensity, increased achiral susceptibility ratio values, and preferential orientation of collagen strands along the boarder of tumor margin. The wide‐field Stokes polarimetric SHG microscopy opens a possibility of quick large area imaging of ultrastructural parameters of tissue collagen, which can be used for nonlinear histopathology investigations. Abstract : We employ wide‐field second harmonic generation (SHG) microscopy together with nonlinear Stokes polarimetry for quick ultrastructural investigation of large sample areas in thin histology sections. Wide‐field Stokes polarimetric SHG microscopy opens a possibility of quick large area imaging of ultrastructural parameters of tissue collagen, which can be used for nonlinear histopathology investigations.